Pengaruh Kualitas Pelayanan, Citra Dan Fasilitas Pelayanan Terhadap Kepuasan Pasien (Studi Kasus Di Rumah Sakit Hl Manambai Abdulkadir) - Aprianditah, Mimiek; Yamin, Ahmad; Mansyur Malonga, Win Ariga (Universitas Bina Sarana Informatika, 2024)
This research aims to analyze the influence of service quality, image and service facilities on patient satisfaction at H.L. Hospital. Manambai Abdulkadir. This research uses quantitative methodology and uses descriptive techniques to analyze data. The research sample consisted of 100 respondents who were patients at H.L. Hospital. Manambai Abdulkadir in Sumbawa Besar. Data were analyzed using the Partial Least Square (PLS) method which is included in the Structural Equation Modeling (SEM) domain. The research results show that service quality has a positive and significant effect on patient satisfaction, image has a positive and significant effect on patient satisfaction and facilities have a positive and significant effect on patient satisfaction. Then these three variables are able to influence patient satisfaction at H.L Manambai Abdulkadir Hospital simultaneously